Exploring factors affecting implementation of public private partnership housing projects in Bauchi State, Nigeria - Mohd Azizuddin, Mohd Sani; Sani, Abdulkadir; Ahmed, Usman Shuaibu (2018)
Public Private Partnership (PPP) Housing scheme in Nigeria is intended to complement government effort toward increasing housing stock and providing affordable housing in the country. However, Bauchi state government adopted the construction of 5,000 phases PPP Housing. But 6 years after the commencement of the scheme, only a few numbers of housing units were completed and commissioned. Therefore, it becomes imperative to carry out research on the impact level of those factors affecting the implementation of the scheme. The aim of the study is to investigate impact level of factors affecting the implementation of PPP housing projects in Bauchi state with a view to find out possible ways that will improve the implementation of the scheme. The descriptive and explorative research design was adopted for this study. 54 structured Questionnaires were administered to construction professional’s staff under private housing developers and relevant government agencies in Bauchi state. 42 valid Questionnaires were retrieved and analysed with SPSS software. The result of the quantitative data analysis shows that creation of favourable investment environment and government support have very high Impact on the implementation of Bauchi PPP housing projects. Therefore, this study recommends that government and other stakeholders should give more attention to the creation of favourable investment environment, support in policy formulation and managerial strategies in the future for improving the implementation of PPP housing projects.